2019
DOI: 10.3389/fmicb.2019.02584
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Two Traditional Chinese Medicine Monomers, Berberine and Matrine, on the Quorum Sensing System of Antimicrobial-Resistant Escherichia coli

Abstract: The quorum sensing (QS) system controls bacterial biofilm formation, which is highly related to the virulence and resistance of pathogens. In the present study, the effect of two traditional Chinese medicine (TCM) monomers, berberine and matrine, on biofilm formation and QS-related gene expression of antimicrobial-resistant (AMR) Escherichia coli strains was investigated by laser scanning confocal microscopy (LSCM) observation and real-time PCR. The results indicated a roughly positive relationship between bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 32 publications
1
33
0
1
Order By: Relevance
“…The CLSM, FESEM, and crystal violet staining results also showed that sanguinarine had a significant inhibitory effect on the P. rettgeri biofilm by blocking the expression and formation of biofilm substances, which led to the inactivation of P. rettgeri [ 68 ]. By changing the quorum sensing system, researchers observed that berberine inhibited biofilm formation in drug-resistant E. coli strains [ 86 ].…”
Section: Antibacterial Mechanisms Of Natural Alkaloidsmentioning
confidence: 99%
“…The CLSM, FESEM, and crystal violet staining results also showed that sanguinarine had a significant inhibitory effect on the P. rettgeri biofilm by blocking the expression and formation of biofilm substances, which led to the inactivation of P. rettgeri [ 68 ]. By changing the quorum sensing system, researchers observed that berberine inhibited biofilm formation in drug-resistant E. coli strains [ 86 ].…”
Section: Antibacterial Mechanisms Of Natural Alkaloidsmentioning
confidence: 99%
“…Other alkaloids which can conduct these modulations include the phenothiazines [99][100][101]. Berberine (6), a well-established antimicrobial agent [102][103][104][105], inhibits biofilm formation of drug-resistant E. coli through the downregulation of quorum-sensing related genes [106]. It is available in good yield from several sources, including Berberis vulgaris L. (Berberidaceae), Coptis chinensis Franch.…”
Section: Antibiotic Drug Discoverymentioning
confidence: 99%
“…Screening QS inhibitors from TCM resources has become a new strategy for the development of natural antibacterial agents ( Khider et al, 2019 ). Both Berberine and Matrine are able to inhibit biofilm formation of antimicrobial-resistant E. coli strains through downregulating the QS system, and Berberine is more effective than Matrine ( Sun et al, 2019 ).…”
Section: Inhibitory Mechanism Of Tcm On Antibiotic Resistancementioning
confidence: 99%